Do stock market and banking sectors development promote innovation efficiency? - Low, SW; Albada, A; Ghazali, NA; Nurhatiah Ahmad Chukari (Emerald Group Publishing Ltd, 2024)
Purpose The purpose of this paper is to investigate the impacts of stock market and banking sectors development on a country's efficiency in transforming its innovation input into output. Design/methodology/approach This study employs a generalized method-of-moments panel estimator to examine the role of stock market and banking development in influencing innovation efficiency. Findings Findings show that a country's stock market development is positively related to its innovation efficiency ratio. Countries with more developed stock markets have relatively higher efficiency in transforming innovation input into innovation output than those with less developed stock markets. There is no evidence that innovation efficiency is influenced by banking sector development. However, when stock market and banking sectors are modeled together, while stock market development retains its positive influence, the findings indicate that banking sector exerts negative impact on innovation efficiency. Practical implications The findings provide useful insights to guide policy decisions for a country's innovation agenda in enhancing its innovation performance. The findings imply that stock market development should be embraced as one of the key policy areas in order for a country to be more efficient in transforming its innovation input into innovation output. Originality/value This paper provides first evidence using data sourced from Global Innovation Index report, first available in 2007 and published by Cornell University, INSEAD and the World Intellectual Property Organization.